2013
DOI: 10.1371/journal.pone.0075756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Microwave on Healing of Fractures with Titanium Alloy Internal Fixation: An Experimental Study in a Rabbit Model

Abstract: BackgroundMicrowave is a method for improving fracture repair. However, one of the contraindications for microwave treatment listed in the literature is surgically implanted metal plates in the treatment field. The reason is that the reflection of electromagnetic waves and the eddy current stimulated by microwave would increase the temperature of magnetic implants and cause heat damage in tissues. Comparing with traditional medical stainless steel, titanium alloy is a kind of medical implants with low magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…When applied to the subjects with titanium alloy implants in this study, this dose of microwave treatments caused apoptosis in the muscles Enhancement of Apoptosis by Titanium Alloy during Microwave Treatments around the implants. In previous experiments, we found that 25 W microwave treatment did not cause damage to the bone tissues and cells around titanium alloy internal fixations between the implanted and the non-implanted control group [13]. TUNEL assays of bone tissues also showed that 40 W microwave treatment also did not cause obvious damage to the bone cells in both the implanted group and the non-implanted control group (S1 Fig). The TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling) technique has been described as a sensitive method for the detection of apoptotic nuclei in tissues and the preferential staining of apoptotic strand breaks.…”
Section: Discussionmentioning
confidence: 68%
“…When applied to the subjects with titanium alloy implants in this study, this dose of microwave treatments caused apoptosis in the muscles Enhancement of Apoptosis by Titanium Alloy during Microwave Treatments around the implants. In previous experiments, we found that 25 W microwave treatment did not cause damage to the bone tissues and cells around titanium alloy internal fixations between the implanted and the non-implanted control group [13]. TUNEL assays of bone tissues also showed that 40 W microwave treatment also did not cause obvious damage to the bone cells in both the implanted group and the non-implanted control group (S1 Fig). The TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling) technique has been described as a sensitive method for the detection of apoptotic nuclei in tissues and the preferential staining of apoptotic strand breaks.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies in vivo and in vitro suggested that a low dose of microwaves reduced edema [2,41]. It also reduced pain by facilitating the 'pain gate' mechanism [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, various RF exposures have been reported to result in burns in the tissues secondary to the increased temperature on the implanted metals. [41] It was reported that 900 and 1800 MHz plane waves can result in temperature rises around the implant with less than 0.25 C and 0.10 C, respectively. [42] On the other hand, compared to stainless steel, titanium alloy, which is frequently preferred in medical implants, have low magnetic permeability and electric conductivity.…”
Section: Histopathological Analysismentioning
confidence: 99%